2008
DOI: 10.1088/0004-6256/136/5/2214
|View full text |Cite
|
Sign up to set email alerts
|

CCD Positions of Saturn and Its Major Satellites From 2002-2006

Abstract: This paper presents 2154 precise positions of Saturn and its major satellites from 359 CCD exposures taken with the 1 m telescope at the Yunnan Observatory during the years 2002-2006. It also describes the improved image-processing techniques for the pixel positional measurement of Saturn's rings and its major satellites, especially for Mimas and Enceladus. The four bright satellites S3-S6 (i.e., Tethys, Dione, Rhea, and Titan) of Saturn are used to calibrate the CCD field of view by comparing their pixel posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…suggesting that some terms could be missing in this model, including Titan's effect on Mimas' orbit. This is consistent with Peng et al (2008) who found a significant periodic signal in their Mimas (O-C) residuals compared to the TASS1.7 ephemeris, based on ground-based astrometric observations.…”
Section: Frequency Analysissupporting
confidence: 90%
“…suggesting that some terms could be missing in this model, including Titan's effect on Mimas' orbit. This is consistent with Peng et al (2008) who found a significant periodic signal in their Mimas (O-C) residuals compared to the TASS1.7 ephemeris, based on ground-based astrometric observations.…”
Section: Frequency Analysissupporting
confidence: 90%
“…The USNO Flagstaff transit circle data, already included in COSS08, has been updated until 2009. Observations from (Peng et al 2008) have also been added. Moreover the highly accurate astrometric observations provided by the observation of the mutual phenomena of Saturnian satellites during 1995 and 2009 have been added.…”
Section: The Observation Setmentioning
confidence: 99%
“…We give only the outline of these techniques. Interested readers can refer to Peng et al (2003) or Peng et al (2008b) for more details. For the pixel position of Jupiter, our technique involves isolating the disc of Jupiter by creating a subimage.…”
Section: Observations and Image Processingmentioning
confidence: 99%